Geochemical survey of hot and cold waters around the Misti volcano, Peru - Cruz Pauccara, Vicentina (2007)
Trabajo presentado en la "2nd Alexander von Humboldt Conference on The Role of Geophysics in Natural Disaster Prevention", realizado en Lima, Perú, el 5-9 marzo 2007.